2021
DOI: 10.1002/advs.202101516
|View full text |Cite
|
Sign up to set email alerts
|

Proximity‐Induced Novel Ferromagnetism Accompanied with Resolute Metallicity in NdNiO3 Heterostructure

Abstract: Employing X-ray magnetic circular dichroism (XMCD), angle-resolved photoemission spectroscopy (ARPES), and momentum-resolved density fluctuation (MRDF) theory, the magnetic and electronic properties of ultrathin NdNiO 3 (NNO) film in proximity to ferromagnetic (FM) La 0.67 Sr 0.33 MnO 3 (LSMO) layer are investigated. The experimental data shows the direct magnetic coupling between the nickelate film and the manganite layer which causes an unusual ferromagnetic (FM) phase in NNO. Moreover, it is shown the metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[ 14,15 ] In contrast, PM NdNiO 3 becomes ferromagnetic (FM) when sandwiched by La 0.67 Sr 0.33 MnO 3 layers. [ 16 ] Interfacial FM also emerges in the PM SrIrO 3 layer in proximity to the La 0.7 Sr 0.3 MnO 3 or LaCoO 3 FM layers. [ 17–19 ] These results are usually understood by the concept of magnetic proximity effect: when two oxides are in close contact, the hybridization of adjacent atomic orbitals produces low‐lying molecular orbits thus interlayer charge transfer and exchange interaction according to the Goodenough–Kanamori–Anderson rules, [ 20–22 ] transferring magnetic order from FM layer to adjacent layers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,15 ] In contrast, PM NdNiO 3 becomes ferromagnetic (FM) when sandwiched by La 0.67 Sr 0.33 MnO 3 layers. [ 16 ] Interfacial FM also emerges in the PM SrIrO 3 layer in proximity to the La 0.7 Sr 0.3 MnO 3 or LaCoO 3 FM layers. [ 17–19 ] These results are usually understood by the concept of magnetic proximity effect: when two oxides are in close contact, the hybridization of adjacent atomic orbitals produces low‐lying molecular orbits thus interlayer charge transfer and exchange interaction according to the Goodenough–Kanamori–Anderson rules, [ 20–22 ] transferring magnetic order from FM layer to adjacent layers.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent works showed that the exchange-bias effect generally existed in LNO/FM-oxide heterostructures, such as LNO/La 2/3 Sr 1/3 MnO 3 (LSMO) and LNO/La 2/3 Ca 1/3 MnO 3 . , These results are interesting because the PM LNO layers have generated magnetic pining to the neighboring FM layers. This implies the development of magnetic order in the LNO layers, which is usually understood by the concept of the magnetic proximity effect. However, there is still controversy regarding the magnetic ground state of LNO layers. On the basis of the polarization-dependent resonant X-ray reflectivity (XRR) experiments, Gibert et al declared that the ultrathin (111)-LNO layer sandwiched between LMO layers was in an antiferromagnetic state with a (1/4, 1/4, 1/4) wavevector .…”
mentioning
confidence: 99%